How to survive anything, anywhere survival skills for every scenario and environment - McNab, Chris (Amber Books, 2018)
Heavily illustrated throughout with more than 500 line artworks and diagrams, How to Survive Anything Anywhere gives the reader practical measures of survival which are easy to memorise and apply: it is a vital single source of invaluable survival information.